Perubahan Iklim sebagai Ancaman terhadap Keamanan Pangan di Indonesia - Dea Amanda (Lembaga Pengembangan Kinerja Dosen, 2026)
Climate change is a global issue that not only impacts the environment but also threatens a country's food security. Indonesia, as a country that relies heavily on the agriculture, fisheries, and livestock sectors, faces high vulnerability to climate change. This study aims to analyze the impact of climate change on the agriculture, livestock, and fisheries sectors. This study used a qualitative method with a literature study approach through data analysis derived from scientific journals, books, and institutional reports. The results of the study indicate that climate change has a significant impact on these three sectors through changes in weather, rainfall patterns, and extreme weather. The El Niño phenomenon can reduce agricultural production, reduce livestock productivity, and disrupt fishermen's catches. These conditions can disrupt national food availability and stability and can increase social and economic vulnerability of the community. Therefore, climate change can be seen as a non-traditional threat to Indonesia's food security, requiring sustainable adaptation efforts to maintain food security in the future.